Innovative stylistic resources in Eugenio Montale's recent poetry - Sansalvadore, Giovanna (My University, 2015)
This thesis sets out firstly to review the recent Italian and non-Italian bibliography on the problems in Montale's last three volumes. The opening chapter shows how the Nobel prize winning poet's manner altered sharply after La bufera e altro with the collection Satura (1971). It reviews the major responses to Satura, before passing on to a rasseqna of responses to the two M a r i , Quaderno and Altri versi. Having covered the new critical tradition it analyzes Montale's typographical presentation of long, short, titled, untitled, free, rhyming, epigrammatic, punning, polemical, lyric, semi-serious, tendentiously polemical or whimsically anti-literary poems. The second chapter considers the texts' studied 'occasionalness1 and apparent 'anti-poeticity', as well as component parts which break this pattern. The study admits that Montale's recent production does not stand the test of high lyric perfection which most commentators detect in Ossi, Occasion! and Bufera. Chapter 111 considers the M a r i , Quaderno and Altri versi as (a) Montale's assiduous annotation of a modus vivendi in our own time, (b) a dissolution and relativization of all interpretations of time, (c) the 'permanent oxymoron' of the recent years, present in Satura but now flowering in the lack of affirmation and negation, in short, the constant and oscillating and uncertain affirmation of contraries, (d) lists, elenchus, (e) the linguistic privileging of totem fauna and talismanic objects, (e) enumeration as well as elenchus, of sub-species of items scarcely relevant to the poet's immortality and so forth. As an example of our line of enquiry we recall the slapping water in v.7 of 'Casa sul mare' (1927), 'Un altro, altra acqua, a tratti...', where semantic effect is subordinated to the genderless trap set by water in eternal motion; mindful always of Montale's own warning that his reader can be 'depistato' by his work and its effects, we refuse to be 'misdirected', in this thesis, by the poet's biography or prose criticism. There are four Appendices which give a selection of colloquial harms used in the three collections, as well as a complete listing of animals., parentheses and foreign words. We have attempted to show that poetry, that supremely useless human occupation, is part of art after all.
A Dissertation submitted to the Faculty of Arts, University of the Witwatersrandj Johannesburg for the Degree of Master of Arts Johannesburg 1982